Metal-clad laminate roll and method for manufacturing same

By sandwiching high stiffness sheets between the layers of the metal-covered laminated plates and using high winding tension, the wrinkles and ribs during winding are solved, the winding stability and planarity are improved, and the metal layer is avoided. Friction damage and dirt transfer.

CN119212863AInactive Publication Date: 2024-12-27KURARAY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380039263.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-15
Filing Date
2023-06-06
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When the flexible metal laminated plate is rolled into a roll, problems such as scars, dirt transfer, adhesion, wrinkles and ribs are easily generated, and the prior art is difficult to effectively prevent the occurrence of these defects.

Method used

The sheet with a specific high stiffness is sandwiched between the layers of the metal-covered laminated plate, and the generation of wrinkles and ribs are suppressed and frictional damage of the metal layer is prevented by high winding tension and appropriate sheet width ratio.

Benefits of technology

It effectively prevents wrinkles and blasts during winding, improves the planarity and stability of the metal-covered laminated plate, and avoids friction damage and dirt transfer of the metal layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212863A_ABST
    Figure CN119212863A_ABST
Patent Text Reader

Abstract

Provided is a metal-clad laminate roll capable of preventing the occurrence of ribs and wrinkles. The metal-clad laminate roll is obtained by winding a metal-clad laminate having a metal layer on at least one surface of a resin film together with a sheet in a roll shape, and the sheet has a stiffness of 0.010 mN or more as measured in accordance with JIS L 1096 2010 8.22.1 A method stiffness (Gurley method). For example, at least the surface of the sheet of the metal-clad laminate roll may be made of a non-metallic material.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related Applications

[0002] This application claims the benefit of priority based on Japanese Patent Application No. 2022-096573, filed on June 15, 2022, the entirety of which is hereby incorporated by reference as a part of this application. Technical Field

[0003] The present invention relates to a metal-clad laminate roll obtained by winding a metal-clad laminate having a metal layer on at least one surface of a resin film together with a sheet into a roll shape. Background Art

[0004] Most flexible film materials such as resin films are ultimately rolled up and shipped, but there is a problem of product defects when rolled up. For example, Patent Document 1 (Japanese Patent Publication No. 2010-83092) describes that due to the high edge of the end when rolled up, the film ruptures at the end or the poor planarity such as the end sagging is induced, which reduces the production stability in the post-processing process. In Patent Document 1, the high edge of the end is prevented by rolling up the resin film in a state where a protective film narrower than the resin film is laminated on at least one side of the resin film.

[0005] Flexible metal-clad laminates having a metal layer on one or both sides of a resin film are also shipped in the form of a rolled product when facing the user. However, when the rolled metal-clad laminate is unrolled, there is a problem that the metal foils rub against each other and cause scratches in the case of a double-sided metal-clad laminate, and the dirt on the surface of the metal foil is transferred to the opposite resin film surface in the case of a single-sided metal-clad laminate. In addition, metal-clad laminates formed with a metal layer by vapor deposition or sputtering have the following problems: if the surface of the metal layer is rubbed, the metal layer is peeled off due to scratches, etc.

[0006] Patent document 2 (Japanese Patent Gazette No. 6648800) describes the following problems: when a long resin film with a metal seed layer formed on both sides by a vacuum film forming method such as sputtering is rolled into a roll in a vacuum film forming device without air inclusion, the metal seed layers stick to each other, and when the long resin film is unrolled from the roll, one side of the metal seed layer is partially peeled off; when a long resin film with a metal seed layer formed on one side is strongly rolled into a roll in a vacuum film forming device without air inclusion, the metal seed layer just after film formation contacts the back side of the long resin film and partially sticks. Patent document 2 describes the following method: In order to avoid these problems, when a long resin film with a metal seed layer formed on it is rolled into a roll, a long spacer paper is sandwiched between the layers and the film is rolled up.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2010-83092

[0010] Patent Document 2: Japanese Patent No. 6648800 Summary of the invention

[0011] Problems to be solved by the invention

[0012] When a flexible metal-clad laminate is wound into a roll, in addition to the generation of scratches, transfer of dirt, and adhesion, there are also problems such as wrinkles caused by the looseness during winding due to the metal layer. The inventors of the present invention have found that wrinkles generated during winding can be dealt with by winding at a high winding tension. However, on the other hand, as a new issue, it has been found that if winding is carried out at a high winding tension, it is easy to generate uneven thickness accumulation of the metal-clad laminate, resulting in ribs.

[0013] Patent Document 1 does not describe a technical concept of suppressing the occurrence of winding wrinkles due to strain caused by the presence of a metal layer, because a protective film having cushioning properties is wound together with the resin film to prevent the edge of the resin film from having a high side.

[0014] In Patent Document 2, although a long strip of spacer paper is wound together with a metal-clad laminate formed by a vacuum film forming method such as sputtering, the purpose is only to prevent the sticking phenomenon, and therefore there is no description of a technical concept of suppressing the generation of winding wrinkles.

[0015] Therefore, an object of the present invention is to provide a metal-clad laminate roll which can prevent wrinkles from being generated and suppress the generation of ribs when a flexible metal-clad laminate is wound into a roll.

[0016] Methods used to solve problems

[0017] The inventors of the present invention have conducted in-depth research to achieve the above-mentioned objectives, and as a result, have found that when a metal-clad laminate having a metal layer on at least one side of a resin film is wound into a roll, by sandwiching a sheet having a specific high stiffness between the layers of the metal-clad laminate and winding it together, the occurrence of wrinkles and ribs can be suppressed, thereby completing the present invention.

[0018] That is, the present invention can be constituted in the following aspects.

[0019] [Method 1]

[0020] A metal-clad laminate roll, wherein a metal-clad laminate having a metal layer on at least one surface of a resin film is wound into a roll together with a sheet, wherein the stiffness of the sheet measured according to JIS L 10962010 8.22.1 A method stiffness (Gurley method) is 0.010 mN or more (preferably 0.015 mN or more, more preferably 0.020 mN or more).

[0021] [Method 2]

[0022] The metal-clad laminate roll according to aspect 1, wherein at least a surface of the sheet is made of a non-metallic material.

[0023] [Method 3]

[0024] The metal-clad laminate roll according to aspect 1 or 2, wherein the dielectric constant of the resin film is 3.5 or less (preferably 3.4 or less, more preferably 3.3 or less).

[0025] [Method 4]

[0026] The metal-clad laminate coil according to any one of aspects 1 to 3, wherein the metal-clad laminate has a stiffness measured according to JIS L 1096 2010 8.22.1 A method stiffness (Gurley method) of 300 mN or less (preferably 250 mN or less, more preferably 200 mN or less, and even more preferably 150 mN or less).

[0027] [Method 5]

[0028] The metal-clad laminate coil according to any one of aspects 1 to 4 satisfies the following formula (1), wherein the stiffness of the metal-clad laminate measured in accordance with JIS L 1096 2010 8.22.1 A method stiffness (Gurley method) is X [mN] and the stiffness of the sheet is Y [mN].

[0029] Y≥0.00007X+0.01 (1)

[0030] [Method 6]

[0031] A method for manufacturing a metal-clad laminate coil, which is a method for manufacturing a metal-clad laminate coil, wherein a long strip of metal-clad laminate and a long strip of sheet are wound up while sandwiching the sheet between layers of the metal-clad laminate, wherein the stiffness of the sheet measured according to JIS L 1096 2010 8.22.1 A method stiffness (Gurley method) is 0.010 mN or more (preferably 0.015 mN or more, more preferably 0.020 mN or more).

[0032] [Method 7]

[0033] The method for producing a metal-clad laminate roll according to Embodiment 6, wherein the winding tension of the metal-clad laminate is 10 N or more (preferably 20 N or more, more preferably 30 N or more).

[0034] As used in this specification, the singular forms, "a", "an" and "the", unless the content clearly indicates otherwise, are intended to include plural forms including "at least one". As used in this specification, the terms "and / or", "at least one" and "more than one" include any and all combinations of the associated listed items.

[0035] It should be noted that any combination of at least two constituent elements disclosed in the claims and / or the specification and / or the drawings is included in the present invention. In particular, any combination of two or more claims recorded in the claims is included in the present invention.

[0036] Effects of the Invention

[0037] The metal-clad laminate coil of the present invention can prevent the generation of wrinkles and ribs. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The present invention can be more clearly understood by the following description of preferred embodiments with reference to the accompanying drawings. However, the embodiments and the accompanying drawings are for illustration and description only and should not be used to define the scope of the present invention. The scope of the present invention is determined by the claims. In the accompanying drawings, the same reference numerals in multiple drawings represent the same parts. The drawings are not necessarily shown to a fixed scale and are exaggerated when expressing the principles of the present invention.

[0039] Figure 1 This is a schematic perspective view showing one embodiment of the metal-clad laminate roll of the present invention.

[0040] Figure 2 This is a schematic perspective view showing one embodiment of the metal-clad laminate roll of the present invention.

[0041] Figure 3 This is a schematic perspective view showing one embodiment of the metal-clad laminate roll of the present invention. DETAILED DESCRIPTION

[0042] In the metal-clad laminate roll of the invention, the metal-clad laminate having a metal layer on at least one surface of a resin film is wound into a roll together with a sheet. Figure 1 1 is a schematic perspective view showing one embodiment of the metal-clad laminate coil of the present invention. Figure 1As shown, for example, in a metal-clad laminate roll 10 , a metal-clad laminate 1 and a sheet 2 are wound together around a winding core 3 (winding core) with the sheet 2 sandwiched between layers of the metal-clad laminate 1 . Figure 1 In the metal-clad laminate roll 10, the widths of the metal-clad laminate 1 and the sheet 2 are the same. In this case, since the edge of the sheet is not pressed, the winding tension of the metal-clad laminate can be increased, and the winding deviation of the edge during transportation can be prevented.

[0043] The widths of the metal-clad laminate 1 and the sheet 2 may also be different. For example, Figure 2 and 3 Each of them is a schematic perspective view showing one embodiment of the metal-clad laminate roll of the present invention. Figure 2 In the metal-clad laminate roll 20, the width of the sheet 2 is wider than the width of the metal-clad laminate 1. When the width of the sheet is wider than the width of the metal-clad laminate, for example, when the width of the metal-clad laminate is set to W, the width of the sheet is preferably W+2mm or more, more preferably W+5mm or more. In addition, when the width of the metal-clad laminate is set to W, the width of the sheet is preferably 1.2×W or less, more preferably 1.1×W or less. In this case, it is possible to avoid contact between the metal-clad laminates, so that the generation of scratches, the transfer of dirt, and the adhesion phenomenon can be more reliably suppressed.

[0044] on the other hand, Figure 3 In the metal-clad laminate roll 30, the width of the sheet 2 is narrower than the width of the metal-clad laminate 1. When the width of the sheet is narrower than the width of the metal-clad laminate, when the width of the metal-clad laminate is set to W, the width of the sheet is preferably less than W-2 mm, and more preferably less than W-5 mm. In addition, when the width of the metal-clad laminate is set to W, the width of the sheet is preferably greater than 0.8×W, and more preferably greater than 0.9×W. Depending on the shape of the edge portion of the metal-clad laminate, bulges (high edges) of the edge portion are sometimes generated when it is rolled into a roll. By making the width of the sheet narrower than the width of the metal-clad laminate as described above, the edge portion of the sheet does not overlap with the edge portion of the metal-clad laminate, thereby more reliably suppressing the bulge of the edge portion of the metal-clad laminate generated during winding.

[0045] The metal-clad laminate coil may include a winding core (winding core), and the outer diameter of the winding core may be 50 to 300 mm, preferably 70 to 250 mm, and more preferably 80 to 200 mm. For the metal-clad laminate coil of the present invention, even if a winding core with a small outer diameter (for example, 50 to 150 mm, preferably 50 to 100 mm) is used to increase the winding length, the generation of wrinkles and ribs can be suppressed. As a winding core, a known winding core such as a plastic core, a paper core (paper tube), a resin-impregnated core, and a metal core can be used. From the perspective of light weight and strength, a plastic core is preferably used. As the material of the plastic core, polyolefins (polyethylene, polypropylene, etc.), acrylonitrile-butadiene-styrene copolymers (ABS resins), polycarbonates, polystyrene, polyvinyl chloride, fiber reinforced plastics (FRP), etc. can be listed. In addition, from the perspective of winding, a resin-impregnated core with excellent surface smoothness is also preferred. As a resin-impregnated core, a resin-impregnated core formed by impregnating a paper core with a resin is preferably used. Examples of the impregnation resin include phenol resin and epoxy resin.

[0046] The stiffness (hereinafter referred to as stiffness) measured according to JIS L 1096 2010 8.22.1 A method stiffness (Gurley method) of the sheet is more than 0.010mN. Stiffness refers to an index that represents the flexibility of the sheet with the bending resilience relative to the load bending. The higher the value, the more difficult it is to bend, and the harder the sheet is. In the present invention, when the metal-clad laminate is wound into a roll, if the sheet with a specific high stiffness is wound together between the layers of the metal-clad laminate, even if it is wound with a high winding tension in order to suppress the generation of wrinkles, the sheet will not follow the uneven thickness of the metal-clad laminate. Therefore, by making the sheet with a specific high stiffness be located between the layers of the metal-clad laminate, the accumulation of uneven thickness of the metal-clad laminate can be prevented, and the generation of violent tendons can be suppressed. The stiffness of the sheet may preferably be 0.015 mN or more, more preferably 0.020 mN or more, and further preferably 0.025 mN or more. In addition, from the viewpoint of having flexibility for winding into a roll, the stiffness of the sheet may be 3.5 mN or less, preferably 3.0 mN or less, and more preferably 2.5 mN or less. It should be noted that in this specification, the stiffness represents the stiffness in the length direction of the long strip material, and is a value measured by the method described in the embodiments described later.

[0047] As long as the sheet material has the stiffness as described above and can be wound into a roll, there is no particular limitation, and resin films, fiber sheets, etc. can be used, and they can be used alone or in combination. For example, as fiber sheets for sheets, textiles, woven fabrics, non-woven fabrics, papers, etc. composed of natural fibers, regenerated fibers, semi-synthetic fibers, and synthetic fibers can be listed, and the types of fibers can be used alone or in combination. In addition, as resin films for sheets, polyester films, polyamide films, polyolefin films (such as polypropylene films, etc.), acrylic resin films, polystyrene films, polycarbonate films, polyimide films, fluororesin films, thermoplastic liquid crystal polymer films, polyphenylene ether films, polyetheretherketone films, polyethersulfone films, polyphenylene sulfide films, etc. can be listed. In order to prevent scratches caused by friction with the metal layer of the metal-clad laminate, the sheet preferably has a low content of inorganic components (such as inorganic particles, metals, etc.), and is preferably composed of organic components (such as resin components). For example, the sheet can contain more than 80% by weight of organic components, preferably more than 85% by weight, more preferably more than 90% by weight, further preferably more than 98% by weight, and further preferably more than 99.9% by weight. In addition, it is preferred that at least the surface of the sheet is not composed of metal, that is, at least the surface is composed of non-metallic materials.

[0048] The thickness of the sheet material depends on the mechanical properties of the material it is made of, but from the viewpoint of having the stiffness as described above and the flexibility to be wound into a roll, it can be 15 to 500 μm, preferably 20 to 300 μm, and more preferably 25 to 150 μm. By making the thickness of the sheet material within the above range, it is possible to prevent the edge of the metal-clad laminate from bulging, and also to suppress the weight of the metal-clad laminate roll.

[0049] For example, from the viewpoint of preventing the positional displacement of the metal-clad laminate and the sheet in the width direction during the conveyance of the coil product, the sheet may be a material having adhesiveness on the surface, preferably having adhesiveness within a range that allows peeling. For example, the peel strength between the metal-clad laminate and the sheet may be 0.5 N / mm or less, preferably 0.2 N / mm or less, and more preferably 0.1 N / mm or less. The peel strength indicates the strength (N / mm) measured when the metal-clad laminate and the sheet are peeled off according to JIS C 6471:1995 (peeling in a 90° direction).

[0050] The sheet may have various functions. For example, the sheet may contain a rust inhibitor from the viewpoint of preventing oxidation of the metal layer of the metal-clad laminate during storage.

[0051] In addition, from the viewpoint of preventing the adhesion of dirt due to the generation of static electricity, the sheet may contain an antistatic agent to provide an antistatic function.

[0052] The metal-clad laminate may be a single-sided metal-clad laminate having a metal layer on one side of a resin film, or may be a double-sided metal-clad laminate having metal layers on both sides of a resin film. In the present invention, the metal-clad laminate may be a laminate formed by laminating a resin film and a metal layer via an adhesive layer (e.g., an adhesive), and from the viewpoint of making the thickness thinner as a circuit substrate manufacturing material, it is preferably a metal-clad laminate formed by directly laminating a resin film and a metal layer without an adhesive layer.

[0053] The stiffness of the metal-clad laminate can be 300 mN or less, preferably 250 mN or less, more preferably 200 mN or less, and further preferably 150 mN or less. The lower limit of the stiffness of the metal-clad laminate is not particularly limited, and may be 0.1 mN or more. When the metal-clad laminate has high flexibility, wrinkles and ribs are easily generated when it is rolled into a roll, so a winding technology that can suppress the generation of wrinkles and ribs without relying on the flexibility of the metal-clad laminate is needed. For the metal-clad laminate roll of the present invention, even when the metal-clad laminate is within the above-mentioned stiffness range and has high flexibility, the generation of wrinkles and ribs can be suppressed.

[0054] When the stiffness of the metal-clad laminate is X [mN] and the stiffness of the sheet is Y [mN], the following formula (1) can be satisfied.

[0055] Y≥0.00007X+0.01 (1)

[0056] As mentioned above, it is more related to the stiffness than the material and thickness of the sheet, which can suppress the generation of wrinkles and ribs in the metal-clad laminate, but from the perspective of further suppressing their generation, the stiffness of the preferred sheet is correlated with the stiffness of the metal-clad laminate itself. That is, when the stiffness of the metal-clad laminate is large, it is preferred to use a sheet with large stiffness. More specifically, it is preferred to satisfy the linear form of the above formula (1). In addition, from the perspective of further suppressing the generation of wrinkles and ribs in the metal-clad laminate, the metal-clad laminate roll preferably satisfies the following formula (2).

[0057] Y≥0.001X+0.02 (2)

[0058] When the stiffness of the metal-clad laminate is set to X [mN] and the stiffness of the sheet is set to Y [mN], from the viewpoint of further suppressing the formation of wrinkles and ribs in the metal-clad laminate, the ratio X / Y can be less than 5000, preferably less than 3000, more preferably less than 1000, and further preferably less than 550. In addition, it can be greater than 1, preferably greater than 3, and more preferably greater than 5.

[0059] The resin film may be any resin film used as a base film for a flexible metal-clad laminate, and examples thereof include thermoplastic liquid crystal polymer (LCP) films, polyimide (PI) films (especially modified polyimide (MPI) films), fluororesin films (such as polytetrafluoroethylene (PTFE) films, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA) films, tetrafluoroethylene-ethylene copolymer (ETFE) films, etc.), polyphenylene ether (PPE) films, polyetheretherketone (PEEK) films, polyester films (such as polyethylene terephthalate (PET) films, polyethylene naphthalate (PEN) films, etc.), and the like.

[0060] The thickness of the resin film can be appropriately selected according to the purpose of the metal-clad laminate, for example, it can be 10 to 500 μm, preferably 15 to 250 μm, and more preferably 25 to 150 μm. For the metal-clad laminate roll of the present invention, in the case of a thinner resin film in the above range (for example, 10 to 150 μm), the metal-clad laminate having the resin film has higher flexibility, and even in the case where ribs and wrinkles are easily generated when rolled into a roll, the generation of wrinkles and ribs can be suppressed.

[0061] The stiffness of the resin film may be 10 mN or less, preferably 5.0 mN or less, and more preferably 2.5 mN or less. The lower limit of the stiffness of the resin film is not particularly limited, and may be 0.001 mN or more. For the metal-clad laminate roll of the present invention, the resin film is within the above-mentioned stiffness range, and the metal-clad laminate has high flexibility, and even in the case where ribs and wrinkles are easily generated when rolled into a roll, the generation of wrinkles and ribs can be suppressed.

[0062] From the viewpoint of use as a high-frequency circuit substrate material, the dielectric constant of the resin film is preferably 3.5 or less, more preferably 3.4 or less, and further preferably 3.3 or less. In addition, the dielectric constant of the resin film is preferably 2.5 or more, more preferably 2.7 or more, and further preferably 2.8 or more. It should be noted that, in general, the dielectric constant can be calculated by multiplying the relative dielectric constant by the dielectric constant of a vacuum (=8.855×10 -12 It should be noted that in this specification, the dielectric constant of a resin film means a dielectric constant in a planar direction and is a value measured by a method described in Examples described later.

[0063] As the resin film, a thermoplastic liquid crystal polymer film is preferred from the viewpoint of excellent high frequency characteristics, and a polyimide film or a fluororesin film is preferred from the viewpoint of excellent heat resistance.

[0064] The thermoplastic liquid crystal polymer film is composed of a thermoplastic liquid crystal polymer. The thermoplastic liquid crystal polymer is composed of a liquid crystal polymer that can be melt-formed (or a polymer that can form an optically anisotropic melt phase). As long as it is a liquid crystal polymer that can be melt-formed, its chemical composition is not particularly limited, and examples thereof include thermoplastic liquid crystal polyesters, or thermoplastic liquid crystal polyester amides into which amide bonds are introduced.

[0065] The thermoplastic liquid crystal polymer may be a polymer in which an imide bond, a carbonate bond, a carbodiimide bond, an isocyanate-derived bond, such as an isocyanurate bond, is further introduced into an aromatic polyester or an aromatic polyester amide.

[0066] As specific examples of the thermoplastic liquid crystal polymer used in the present invention, there can be listed well-known thermoplastic liquid crystal polyesters and thermoplastic liquid crystal polyester amides derived from the compounds classified as (1) to (4) and their derivatives exemplified below. However, it is self-evident that there is an appropriate range for the combination of various raw material compounds in order to form a polymer capable of forming an optically anisotropic melt phase.

[0067] (1) Aromatic or aliphatic diols (see Table 1 for representative examples)

[0068]

[0069] (2) Aromatic or aliphatic dicarboxylic acids (see Table 2 for representative examples)

[0070]

[0071] (3) Aromatic hydroxycarboxylic acid (see Table 3 for representative examples)

[0072]

[0073] (4) Aromatic diamine, aromatic hydroxylamine or aromatic aminocarboxylic acid (see Table 4 for representative examples)

[0074]

[0075] As representative examples of thermoplastic liquid crystal polymers obtained from these raw material compounds, copolymers having repeating units shown in Tables 5 and 6 can be cited.

[0076]

[0077]

[0078] Among these copolymers, copolymers containing at least p-hydroxybenzoic acid and / or 6-hydroxy-2-naphthoic acid as repeating units are preferred, and particularly preferred are (i) copolymers containing repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid; or (ii) copolymers containing repeating units of at least one aromatic hydroxycarboxylic acid selected from the group consisting of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid and at least one aromatic diol and / or an aromatic hydroxyamine and at least one aromatic dicarboxylic acid.

[0079] For example, in the copolymer of (i), when the thermoplastic liquid crystal polymer contains at least repeating units of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, the molar ratio (A) / (B) of the repeating unit (A) of p-hydroxybenzoic acid to the repeating unit (B) of 6-hydroxy-2-naphthoic acid in the thermoplastic liquid crystal polymer is preferably (A) / (B) = about 10 / 90 to about 90 / 10, more preferably (A) / (B) = about 15 / 85 to about 85 / 15, and further preferably (A) / (B) = about 20 / 80 to about 80 / 20.

[0080] In the case of the copolymer (i), in addition to the repeating units derived from p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, from the viewpoint of adjusting the molecular weight, etc., repeating units derived from aromatic diols or aromatic dicarboxylic acids (for example, terephthalic acid) may be contained.

[0081] In the case of the copolymer of (ii), at least one aromatic hydroxycarboxylic acid (C) selected from the group consisting of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid, at least one aromatic diol (D) selected from the group consisting of 4,4'-dihydroxybiphenyl, hydroquinone, phenylhydroquinone and 4,4'-dihydroxydiphenyl ether, and at least one aromatic dicarboxylic acid (E) selected from the group consisting of terephthalic acid, isophthalic acid and 2,6-naphthalene dicarboxylic acid are contained in the thermoplastic liquid crystal polymer. The molar ratio may be the aromatic hydroxycarboxylic acid (C): the aromatic diol (D): the aromatic dicarboxylic acid (E) = about (30-80): about (35-10): about (35-10), and may be more preferably (C): (D): (E) = about (35-75): about (32.5-12.5): about (32.5-12.5), and may be further preferably (C): (D): (E) = about (40-70): about (30-15): about (30-15).

[0082] In addition, the molar ratio of the repeating unit derived from 6-hydroxy-2-naphthoic acid in the aromatic hydroxycarboxylic acid (C) may be, for example, 85 mol% or more, preferably 90 mol% or more, and more preferably 95 mol% or more. The molar ratio of the repeating unit derived from 2,6-naphthalenedicarboxylic acid in the aromatic dicarboxylic acid (E) may be, for example, 85 mol% or more, preferably 90 mol% or more, and more preferably 95 mol% or more.

[0083] In addition, the aromatic diol (D) may be repeating units (D1) and (D2) derived from two different aromatic diols selected from the group consisting of hydroquinone, 4,4'-dihydroxybiphenyl, phenylhydroquinone and 4,4'-dihydroxydiphenyl ether. In this case, the molar ratio of the two aromatic diols may be (D1) / (D2)=23 / 77 to 77 / 23, more preferably 25 / 75 to 75 / 25, and even more preferably 30 / 70 to 70 / 30.

[0084] The molar ratio of the repeating structural unit derived from the aromatic diol to the repeating structural unit derived from the aromatic dicarboxylic acid is preferably (D) / (E) = 95 / 100 to 100 / 95. Outside this range, the degree of polymerization does not increase and the mechanical strength tends to decrease.

[0085] It should be noted that the molten phase capable of forming optical anisotropy in the present invention can be identified by, for example, placing a sample on a hot stage, heating it under a nitrogen atmosphere, and observing the transmitted light of the sample.

[0086] As the thermoplastic liquid crystal polymer, preferably a melting point (hereinafter referred to as Tm 0 ) For example, a thermoplastic liquid crystal polymer in the range of 200 to 360°C, preferably Tm 0 Thermoplastic liquid crystal polymers having a Tm in the range of 240 to 350°C, preferably Tm 0 Thermoplastic liquid crystal polymers of 260 to 330°C. It should be noted that the melting point of the thermoplastic liquid crystal polymer can be obtained by observing the thermal behavior of the thermoplastic liquid crystal polymer sample using a differential scanning calorimeter. That is, the thermoplastic liquid crystal polymer sample can be heated from room temperature (e.g., 25°C) at a rate of 10°C / min to completely melt, and then the melt is cooled to 50°C at a rate of 10°C / min, and then heated again at a rate of 10°C / min, and the position of the endothermic peak that appears at this time is recorded as the melting point of the thermoplastic liquid crystal polymer sample.

[0087] In addition, from the viewpoint of melt moldability, the thermoplastic liquid crystal polymer may have a melt viscosity of, for example, 30 to 120 Pa·s, preferably 50 to 100 Pa·s, where the melt viscosity (Tm 0Melt viscosity at a shear rate of 1000 / s at +20)°C.

[0088] In the above-mentioned thermoplastic liquid crystal polymer, thermoplastic polymers and various additives such as polyethylene terephthalate, modified polyethylene terephthalate, polyolefin, polycarbonate, polyarylate, polyamide, polyphenylene sulfide, polyetheretherketone, and fluororesin can be added within the scope that does not damage the effect of the present invention. In addition, fillers can be added as needed.

[0089] The TLCP film may contain 50 wt % or more of the TLCP, preferably 80 wt % or more, more preferably 90 wt % or more, further preferably 95 wt % or more, and further more preferably 98 wt % or more.

[0090] The thermoplastic liquid crystal polymer film may be a cast film of the thermoplastic liquid crystal polymer or an extrusion film formed by extruding the thermoplastic liquid crystal polymer. In this case, any extrusion molding method may be used, but the well-known T-die film stretching method, laminate stretching method, inflation method, etc. are industrially advantageous.

[0091] In addition, known or customary heat treatment may be performed as needed to adjust the melting point and / or thermal expansion coefficient of the thermoplastic liquid crystal polymer film. The heat treatment conditions may be appropriately set according to the target. For example, the melting point (Tm) of the thermoplastic liquid crystal polymer may be adjusted. 0 )-10°C or above (e.g., about Tm 0 -10℃~about Tm 0 +30°C, preferably about Tm 0 ℃~about Tm 0 +20°C) for several hours to increase the melting point (Tm) of the thermoplastic liquid crystal polymer film.

[0092] The melting point (Tm) of the thermoplastic liquid crystal polymer film may be, for example, 270 to 380° C., preferably in the range of 280 to 370° C. It should be noted that the melting point (Tm) of the thermoplastic liquid crystal polymer film can be obtained by observing the thermal behavior of the thermoplastic liquid crystal polymer film sample using a differential scanning calorimeter. That is, the thermoplastic liquid crystal polymer film sample can be heated from room temperature (for example, 25° C.) at a rate of 10° C. / min, and the position of the endothermic peak that appears at this time can be obtained as the melting point (Tm) of the thermoplastic liquid crystal polymer film.

[0093] The polyimide film is made of polyimide. The polyimide is not particularly limited as long as it is a polymer having an imide group in a repeating unit, and examples thereof include polyimide-based resins such as polyimide, polyamideimide, polybenzimidazole, polyimide ester, polyetherimide, and polysiloxaneimide.

[0094] Polyimide can be formed by imidizing (curing) the polyamic acid as a precursor. Polyamic acid can be synthesized by reacting a known diamine and a tetracarboxylic acid (including its anhydride) in the presence of a solvent. As diamine, aromatic diamines, aliphatic diamines, alicyclic diamines, etc. can be used. From the viewpoint of heat resistance, aromatic diamines are preferred. As aromatic diamines, for example, 4,4'-diaminodiphenyl ether, 2'-methoxy-4,4'-diaminobenzanilide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxy-4,4'-diaminobiphenyl, 4,4'-diaminobenzanilide, 5-amino-2-(p-aminophenyl)benzoic acid can be cited. Azoles, etc. In addition, as tetracarboxylic acids, aromatic tetracarboxylic acids, aliphatic tetracarboxylic acids, alicyclic tetracarboxylic acids, their anhydrides, etc. can be used. From the viewpoint of heat resistance, aromatic tetracarboxylic anhydrides are preferred. As aromatic tetracarboxylic anhydrides, for example, pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfone tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, etc. can be cited. These diamines and tetracarboxylic acids can be used alone or in combination of two or more.

[0095] The polyimide film can be prepared by, for example, applying a solution of a polyamic acid (polyimide precursor) obtained by reacting a diamine with a tetracarboxylic acid on a support and drying the polyamic acid film, followed by heat treatment to solidify it (imidization). The polyamic acid solution can be applied using known coating methods such as spin coating, comma coating, screen printing, slit coating, roll coating, blade coating, dip coating, and die coating.

[0096] Various additives, fillers, and the like may be added to the polyimide within a range not impairing the effects of the present invention.

[0097] The fluororesin film is made of a fluororesin. The fluororesin is not particularly limited as long as it is a polymer containing fluorine atoms in a repeating unit, and examples thereof include polytetrafluoroethylene (PTFE), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), tetrafluoroethylene-ethylene copolymer (ETFE) and the like.

[0098] The fluororesin film can be produced by a known method, such as casting, extrusion, inflation, etc. Various additives, fillers, etc. may be added to the fluororesin within a range not impairing the effects of the present invention.

[0099] In the resin film, the content of components other than the resin (various additives, fillers, etc.) may be 20 wt % or less, preferably 10 wt % or less, more preferably 5 wt % or less, further preferably 2 wt % or less, and further more preferably 1 wt % or less.

[0100] The metal-clad laminate may be produced by bonding a metal foil to a resin film by thermocompression bonding to form a metal layer, by sputtering, vapor deposition, electroless plating, etc., or by casting a resin on a metal foil.

[0101] The metal forming the metal layer is not particularly limited, and examples thereof include gold, silver, copper, iron, tin, nickel, aluminum, chromium, and alloy metals thereof.

[0102] When a metal foil is used as the metal layer, for example, the metal foil formed of the above metal can be used, and copper foil and stainless steel foil are preferred from the viewpoints of conductivity, operability and cost. As the copper foil, copper foil manufactured by a rolling method or an electrolytic method can be used. In addition, the metal foil can be subjected to a surface treatment such as a roughening treatment that is usually implemented within the range that does not damage the high frequency characteristics of the metal-clad laminate of the present invention.

[0103] In the sputtering method or the vapor deposition method, a process is performed in which a metal portion is brought into contact with a resin film by sputtering or vapor deposition of a metal and the two are bonded. The sputtering method or the vapor deposition method is a method known in the field of electronic substrate manufacturing. Examples of the metal for sputtering or vapor deposition include copper, aluminum, gold, tin, and chromium.

[0104] In the electroless plating method, a process is performed to bond the two by precipitating a metal from a solution containing metal ions onto the surface of a resin film. The electroless plating method is a well-known method in the field of manufacturing products for plating on non-conductive materials (plastics, ceramics, etc.), and examples of the metal include copper, nickel, cobalt, gold, tin, chromium, etc.

[0105] The thickness of the metal layer can be appropriately set according to the purpose of the metal-clad laminate, for example, it can be selected from a wide range of 10 nm to 100 μm. When a metal foil is used as the metal layer, the thickness of the metal layer can be 1 to 100 μm, preferably 5 to 50 μm, and more preferably 8 to 35 μm. In addition, when the metal layer is formed by sputtering, evaporation, electroless plating, etc., the thickness of the metal layer can be 10 nm to 35 μm, preferably 50 nm to 12 μm, and more preferably 100 nm to 9 μm.

[0106] In the metal-clad laminate coil, the coiling length of the metal-clad laminate may be 10 m or more, preferably 20 m or more, and more preferably 30 m or more. Even if the coiling length increases within the above range, the metal-clad laminate coil of the present invention can prevent ribs and wrinkles, and can therefore be used satisfactorily. In addition, from the viewpoint of preventing the metal-clad laminate coil from becoming too heavy, the coiling length of the metal-clad laminate may be 200 m or less.

[0107] The metal-clad laminate coil of the present invention can be manufactured by winding up a long metal-clad laminate and a long sheet while sandwiching the sheet between the layers of the metal-clad laminate. The long metal-clad laminate is not particularly limited as long as it can be wound together with the long sheet, for example, an unwinding coil of the metal-clad laminate manufactured and temporarily wound can be prepared, but from the viewpoint of maintaining the quality of the metal-clad laminate, it is preferred to directly convey the metal-clad laminate manufactured upstream and to coil up the metal-clad laminate while sandwiching the sheet between the layers.

[0108] The winding tension when winding the long metal-clad laminate and the long sheet can be set according to the type, thickness, etc. For example, the winding tension when winding the metal-clad laminate can be 10N or more, preferably 20N or more, and more preferably 30N or more. By winding with a high winding tension, it is possible to prevent winding wrinkles, and it is also possible to prevent the roll from deforming into a bamboo shoot shape, i.e., a string of layers. In addition, the metal-clad laminate roll of the present invention can have a winding strength that does not deform under the random vibration test condition level 1 of JIS Z 0232.

[0109] In addition, the winding tension (N) of the metal-clad laminate is preferably higher than the winding tension (N) of the sheet. For example, the winding tension of the metal-clad laminate may be 1.2 times or more of the winding tension of the sheet, preferably 1.3 times or more, more preferably 1.5 times or more, and may be 5 times or less.

[0110] The metal-clad laminate coil of the present invention can be used to store and transport the metal-clad laminate as a product, and can be unrolled for use when the metal-clad laminate is used for post-processing or downstream product manufacturing. When the metal-clad laminate is unrolled, the sheet material can be separated from the metal-clad laminate and then wound up and recycled using a sheet material winding roller. The recycled sheet material can be reused for the same purpose.

[0111] The metal-clad laminate roll of the present invention can prevent the generation of ribs and wrinkles, so the quality of the rolled metal-clad laminate itself can be maintained for storage and transportation. Such a metal-clad laminate can be used for various purposes depending on the type of resin film and metal layer, for example, it can be used for parts used in the electrical / electronic field, office equipment / precision equipment field, power semiconductor field, etc., and can be effectively used as a circuit board material in particular.

[0112] Example

[0113] The present invention will be described in more detail below by way of examples, but the present invention is not limited by these examples. It should be noted that in the following examples and comparative examples, various physical properties were measured by the following methods.

[0114] [thickness]

[0115] The thickness of various materials was measured using a digital micrometer (manufactured by Mitutoyo Co., Ltd.). For the measurement, the target material was measured at intervals of 1 cm in the width direction, and the average value of 10 points randomly selected from the center and the end was taken as the thickness. It should be noted that the thickness of the copper layer formed by evaporation and electroplating is calculated from the difference between the thickness of the entire copper-clad laminate and the thickness of the thermoplastic liquid crystal polymer film monomer.

[0116] [Stiffness]

[0117] According to JIS L 1096 2010 "Textile Test Methods for Woven and Knitted Fabrics" 8.22.1 A Method Stiffness (Gurley Method), the stiffness (mN) in the longitudinal direction was measured using a Gurley Softness Tester (manufactured by Toyo Seiki Seisaku-sho, Ltd.) using a sample cut into a specified size. A weight of 5 g to 200 g was attached to the sample for measurement. In particular, when a sample with a thickness of 25 μm or less was used, the stiffness was too low, so a weight of 1.5 g was attached for measurement.

[0118] [Dielectric constant]

[0119] The resin film was cut into pieces with a width of 40 mm and a length of 50 mm to prepare a sample sheet. A molecular orientation meter (MOA6015 manufactured by Oji Instruments Co., Ltd.) was used to measure the film plane direction (MD direction) and the direction orthogonal thereto (TD direction) at 23±3°C at 15 GHz, and the dielectric constant of the resin film in the plane direction was calculated as their average value.

[0120] [Peel strength]

[0121] A 3 mm wide peel test piece was prepared from a laminate of a metal-clad laminate and a sheet unrolled from a metal-clad laminate roll, and the strength (N / mm) at the interface between the metal-clad laminate and the sheet when peeling occurred was measured at a speed of 50 mm / min in accordance with JIS C 6471:1995 (90° peeling).

[0122] [Evaluation of wrinkle generation]

[0123] For the copper-clad laminate coils obtained in the embodiments and comparative examples, first visually determine whether winding wrinkles are generated. Here, the irregularly generated concave and convex parts that become striped are judged as wrinkles. In the case where the generation of winding wrinkles cannot be confirmed by visual inspection, it is judged as A+. In the case where the generation of winding wrinkles is confirmed by visual inspection, the part of the copper-clad laminate where winding wrinkles are generated is cut into 15 cm squares, placed on a porous ceramic vacuum chuck table, and adsorbed with an adsorption force of 50 kPa. The case where the adsorption is smooth and the wrinkles disappear is judged as A, the case where the adsorption is at a level without problems in use but there are wrinkles compared to A is judged as B, and the case where it is not smoothly adsorbed and bulges and cannot be used as a product is judged as C.

[0124] [Evaluation of the generation of bulging tendons]

[0125] The copper-clad laminate rolls obtained from the examples and comparative examples are unrolled and visually checked for the presence or absence of ribs. Here, the portion where the thickness of the local coiled material is unevenly stacked and locally bulges or the portion with a concave-convex shape generated by the period of the product roll is judged as a rib. In the case where the occurrence of ribs cannot be confirmed by visual inspection, it is judged as A+. In the case where the occurrence of ribs is confirmed by visual inspection, the portion of the copper-clad laminate where ribs are generated is cut into 15 cm squares in the same manner as the determination of wrinkles, and it is adsorbed on a porous ceramic vacuum chuck. The case where it is smoothly adsorbed and the undulations disappear is judged as A, the case where it is adsorbed at a level that is not problematic in use but has undulations compared to A is judged as B, and the case where it is not smoothly adsorbed and bulges, and there are undulations that cannot be used as a product is judged as C.

[0126] (Example 1)

[0127] When a single-sided copper-clad laminate (QF1-02512 manufactured by Kuraray Co., Ltd., thickness: 25 μm thermoplastic liquid crystal polymer film, 12 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a slightly adhesive PET film (PET75-H2120 manufactured by Nichiei Shinka Co., Ltd., thickness: 75 μm, width: 250 mm) is wound together with the adhesive surface of the thermoplastic liquid crystal polymer film surface of the single-sided copper-clad laminate in contact with the single-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 3 inches and an outer diameter of 84 mm. Regarding the winding tension during winding, the single-sided copper-clad laminate is set to 50 N and the slightly adhesive PET film is set to 20 N. Each is wound up to a length of 100 m to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate was unrolled from the obtained single-sided copper-clad laminate roll, and no wrinkles or ribs were generated. In addition, the peel strength between the single-sided copper-clad laminate and the slightly adhesive PET film was 0.02 N / mm.

[0128] In addition, the thermoplastic liquid crystal polymer film surface of the unrolled single-sided copper-clad laminate was observed at 250 times using a digital microscope (DSX1000 manufactured by Olympus Corporation), and no copper particles were found to be attached. It should be noted that the observation area was carried out at three locations, namely, the two sides and the center of the thermoplastic liquid crystal polymer film surface in the width direction within the range of 100 mm in the length direction and 30 mm in the width direction.

[0129] (Example 2)

[0130] For a thermoplastic liquid crystal polymer film (manufactured by Kuraray Co., Ltd., CTQ-50, thickness: 50 μm, width: 250 mm, dielectric constant: 3.3), a copper vapor deposition layer was continuously formed on the surface of the thermoplastic liquid crystal polymer film by a roll-to-roll method using a vacuum vapor deposition device (manufactured by Rock Giken Kogyo Co., Ltd., RVC-W-300). Next, a copper plating layer was formed on the surface of the copper vapor deposition layer by electroplating to form a copper layer of 6 μm consisting of a copper vapor deposition layer and a copper plating layer, and a single-sided copper-clad laminate was produced. It should be noted that the copper plating layer was formed in a manner in which the copper layer had a thickness of 6 μm by placing it in a high-level plating type copper sulfate basic bath (a copper sulfate plating basic composition containing 100 g / L of copper sulfate and 220 g / L of sulfuric acid).

[0131] When the obtained single-sided copper-clad laminate is wound on the winding core, the anti-rust paper (manufactured by E-PACK Co., Ltd., NKVCI Copack IC-26M, thickness: 15μm, width: 260mm) is wound together in a manner of sandwiching the interlayer of the single-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170mm. Regarding the winding tension during winding, the single-sided copper-clad laminate is set to 60N, and the anti-rust paper is set to 30N. The winding is performed at a length of 30m respectively to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate is unwound from the obtained single-sided copper-clad laminate roll without generating wrinkles and ribs.

[0132] The obtained single-sided copper-clad laminate was rolled up and stored in a constant temperature and humidity chamber (manufactured by Kusumoto Chemicals Co., Ltd., CH321P) at a temperature of 60° C. and a humidity of 40% for 200 hours. No rust was observed on the copper layer of the single-sided copper-clad laminate.

[0133] (Example 3)

[0134] When a single-sided copper-clad laminate (QF1-02512 manufactured by Kuraray Co., Ltd., thickness: 25 μm thermoplastic liquid crystal polymer film, 12 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (Lumirror #25 manufactured by Toray Industries, Ltd., thickness: 25 μm, width: 250 mm) is wound together in a manner of sandwiching between the layers of the single-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the single-sided copper-clad laminate is set to 40 N, and the PET film is set to 20 N. The winding is performed in a length of 100 m, respectively, to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate was unrolled from the obtained single-sided copper-clad laminate roll without generating wrinkles or ribs.

[0135] (Example 4)

[0136] When a two-sided copper-clad laminate (manufactured by Kuraray Co., Ltd., QF1-02512D, thickness: 25 μm thermoplastic liquid crystal polymer film, 12 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (manufactured by Toray Industries, Ltd., Lumirror#75, thickness: 75 μm, width: 240 mm) is wound together in a manner of sandwiching the interlayer of the two-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the two-sided copper-clad laminate is set to 60 N, and the PET film is set to 30 N. The winding is performed at a length of 50 m respectively to obtain a two-sided copper-clad laminate roll. The two-sided copper-clad laminate is unwound from the obtained two-sided copper-clad laminate roll without wrinkles and ribs.

[0137] Assuming transportation, the double-sided copper-clad laminate roll was packed with a corrugated box and tested under the conditions of random vibration test level 1 of JIS Z 0232. The double-sided copper-clad laminate was unrolled from the double-sided copper-clad laminate roll after the test, and the appearance was confirmed over the entire length, and there was no scratch. It should be noted that the stripes with a length of 5 mm or more on the copper foil surface were evaluated as scratches when observed with a 10x magnifying glass.

[0138] (Example 5)

[0139] When a two-sided copper-clad laminate (manufactured by Kuraray Co., Ltd., QF1-05012D, thickness: 50 μm thermoplastic liquid crystal polymer film, 12 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (manufactured by Toray Industries, Ltd., Lumirror#25, thickness: 25 μm, width: 250 mm) is wound together in a manner of sandwiching the interlayer of the two-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the two-sided copper-clad laminate is set to 60 N, and the PET film is set to 40 N. The winding is performed at a length of 50 m respectively to obtain a two-sided copper-clad laminate roll. The two-sided copper-clad laminate is unwound from the obtained two-sided copper-clad laminate roll without wrinkles and ribs.

[0140] (Example 6)

[0141] When a two-sided copper-clad laminate (manufactured by Kuraray Co., Ltd., QF1-10018D, thickness: 100 μm thermoplastic liquid crystal polymer film, 18 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (manufactured by Toray Industries, Ltd., Lumirror #50, thickness: 50 μm, width: 250 mm) is wound together in a manner of sandwiching the interlayer of the two-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the two-sided copper-clad laminate is set to 60 N, and the PET film is set to 45 N. The winding is performed at a length of 50 m respectively to obtain a two-sided copper-clad laminate roll. The two-sided copper-clad laminate is unwound from the obtained two-sided copper-clad laminate roll without wrinkles and ribs.

[0142] (Example 7)

[0143] When a double-sided copper-clad laminate (QF1-20035D manufactured by Kuraray Co., Ltd., thickness: 200 μm thermoplastic liquid crystal polymer film, 35 μm copper foil, width: 540 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (Lumirror #75 manufactured by Toray Industries, Ltd., thickness: 75 μm, width: 500 mm) is wound together in a manner of sandwiching between the layers of the double-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the double-sided copper-clad laminate is set to 100 N, and the PET film is set to 50 N. The winding is performed in a length of 50 m, respectively, to obtain a double-sided copper-clad laminate roll. The double-sided copper-clad laminate was unrolled from the obtained double-sided copper-clad laminate, and no wrinkles or ribs were generated.

[0144] (Example 8)

[0145] When a single-sided copper-clad laminate (QF1-10018 manufactured by Kuraray Co., Ltd., thickness: 100 μm thermoplastic liquid crystal polymer film, 18 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (Lumirror #25 manufactured by Toray Industries, Ltd., thickness: 25 μm, width: 250 mm) is wound together in a manner of sandwiching between the layers of the single-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the single-sided copper-clad laminate is set to 60 N, and the PET film is set to 30 N. 50 m lengths of winding are performed respectively to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate was unrolled from the obtained single-sided copper-clad laminate roll, and wrinkles and streaks were generated only to such an extent that there was no problem in use.

[0146] (Example 9)

[0147] When a single-sided copper-clad laminate (QF1-20035 manufactured by Kuraray Co., Ltd., thickness: 200 μm thermoplastic liquid crystal polymer film, 35 μm copper foil, width: 540 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (Lumirror #25 manufactured by Toray Industries, Ltd., thickness: 25 μm, width: 560 mm) is wound together in a manner of sandwiching between the layers of the single-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the single-sided copper-clad laminate is set to 100 N, and the PET film is set to 30 N. 50 m lengths of winding are performed respectively to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate was unrolled from the obtained single-sided copper-clad laminate roll, and wrinkles and streaks were generated only to such an extent that there was no problem in use.

[0148] (Comparative Example 1)

[0149] A single-sided copper-clad laminate (manufactured by Kuraray Co., Ltd., QF1-02512, thickness: 25 μm thermoplastic liquid crystal polymer film, 12 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) was wound on a winding core. The winding core used an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. The winding tension during winding was set to 50 N, and a 100 m length of winding was performed to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate was unwound from the obtained single-sided copper-clad laminate roll, resulting in wrinkles and ribs.

[0150] (Comparative Example 2)

[0151] When a single-sided copper-clad laminate (manufactured by Kuraray Co., Ltd., QF1-02512, thickness: 25 μm thermoplastic liquid crystal polymer film, 12 μm copper foil, width: 250 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a PET film (manufactured by Toray Industries, Ltd., Lumirror #12, thickness: 12 μm, width: 250 mm) is wound together in a manner of sandwiching the interlayer of the single-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the single-sided copper-clad laminate is set to 60 N, and the PET film is set to 20 N. The winding is performed at a length of 100 m respectively to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate is unwound from the obtained single-sided copper-clad laminate roll, resulting in wrinkles and ribs.

[0152] (Comparative Example 3)

[0153] When a single-sided copper-clad laminate (QF1-20035 manufactured by Kuraray Co., Ltd., thickness: 200 μm thermoplastic liquid crystal polymer film, 35 μm copper foil, width: 540 mm, thermoplastic liquid crystal polymer film dielectric constant: 3.2) is wound on a winding core, a polyethylene film (SF-900 manufactured by Sekisui Chemical Co., Ltd., thickness: 20 μm cut to a width of 500 mm) is wound together in a manner of sandwiching between the layers of the single-sided copper-clad laminate. The winding core uses an ABS core with an inner diameter of 6 inches and an outer diameter of 170 mm. Regarding the winding tension during winding, the single-sided copper-clad laminate is set to 60 N, and the polyethylene film is set to 20 N. Each is wound up to a length of 50 m to obtain a single-sided copper-clad laminate roll. The single-sided copper-clad laminate was unrolled from the obtained single-sided copper-clad laminate roll, and wrinkles and ribs were generated.

[0154]

[0155] Industrial Applicability

[0156] The metal-clad laminate roll of the present invention can be used for various purposes depending on the types of resin film and metal layer, for example, it can be used for components used in the electrical / electronic fields, office equipment / precision equipment fields, power semiconductor fields, etc., and can especially be effectively used as a circuit substrate material.

[0157] As mentioned above, the preferred embodiments of the present invention have been described. However, it is easy for a person skilled in the art to conceive of various changes and modifications within an obvious scope after reading this specification.

[0158] Therefore, such changes and modifications are construed as falling within the scope of the invention as determined by the claims.

[0159] Explanation of symbols

[0160] 10, 20, 30...Metal-clad laminate coils

[0161] 1…Metal-clad laminate

[0162] 2…sheet

[0163] 3…Reeling core

Claims

1. A metal-clad laminate roll, wherein a metal-clad laminate having a metal layer on at least one surface of a resin film is wound into a roll together with a sheet, wherein: The sheet has a stiffness measured in accordance with JIS L 1096 2010 8.22.1 A method stiffness (Gurley method) of 0.010 mN or more.

2. The metal-clad laminate coil according to claim 1, wherein: At least a surface of the sheet is made of a non-metallic material.

3. The metal-clad laminate coil according to claim 1 or 2, wherein: The resin film has a dielectric constant of 3.5 or less.

4. The metal-clad laminate coil according to any one of claims 1 to 3, wherein The metal-clad laminate is based on JIS L 1096 2010 8.22.1 The stiffness measured by the A method (Gurley method) shall be less than 300 mN.

5. The metal-clad laminate coil according to any one of claims 1 to 4, wherein The metal-clad laminate is based on JIS L 1096 2010 8.22.1 Stiffness by A Method (Gurley Method) When the stiffness measured is X [mN] and the stiffness of the sheet is Y [mN], the following formula (1) is satisfied: Y ≥ 0.00007X + 0.01 (1).

6. A method for producing a metal-clad laminate coil, comprising winding a long metal-clad laminate and a long sheet while sandwiching the sheet between layers of the metal-clad laminate, wherein: The sheet is based on JIS L 1096 2010 8.22.1 The stiffness measured by the A method (Gurley method) shall be not less than 0.010 mN.

7. The method for manufacturing a metal-clad laminate coil according to claim 6, wherein: The winding tension of the metal-clad laminate is 10N or more.

Citation Information

Patent Citations

  • Resin film roll and process for producing the same

    JP2010083092A